Service Quality Judging from the Community Satisfaction Index at the Orchid Medika Clinic, Sumedang Regency - Sutopo (SINTESA, 2022)
Service quality is considered good if the service provided is in accordance with what is expected by consumers, while if it exceeds what consumers expect, it can be said that the service is very satisfying. However, sometimes there are also services that are not expected to match what consumers expect. This service is said to be bad, if the company is deemed unable to fulfill consumer desires, either through products or through company services. Product quality and good service performance will greatly affect customer satisfaction. This research was conducted at the Orchid Medika Clinic Sumedang, to determine the patient satisfaction index at the Orchid Medika clinic. by using a non- probability sampling method, the research instrument in the form of a questionnaire distributed to patients as respondents was determined based on purposive sampling technique. determination of the number of samples based on calculations from Roscoe, where the number of samples based on the calculation of 110 people. Dimensions of service quality Clarity of service procedures, Simplicity of service procedures, Certainty of service time, Accuracy of service products, Security of service products, Responsibility, Completeness of advice and infrastructure, Ease of access to services, Discipline, courtesy and officers, Convenience of location. The analytical tool used is the Microsoft Excel program, which will later be converted back into a service satisfaction index, and the results show that the patient satisfaction index score on the quality of orchid clinic services is at a score of 83 or a very good rating.â€